1992
DOI: 10.1111/j.1600-079x.1992.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blockers in vivo inhibit serotonin N‐acetyltransferase (NAT) activity in chicken retina stimulated by darkness and not by agents elevating intracellular cyclic AMP level

Abstract: The molecular mechanism underlying the role of calcium influx in the regulation of retinal serotonin N-acetyltransferase (NAT) activity was studied in vivo in chickens. Systemic administration of organic antagonists of voltage-sensitive calcium channels (VSCC), i.e., nimodipine and nifedipine, resulted in a marked suppression of the nocturnal increase of NAT activity in chicken retina. In contrast, NAT activity stimulated by nonhydrolysable analogs of cyclic AMP (dibutyryl-cyclic AMP and 8-bromo-cyclic AMP), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…However, such stimulatory effect has, to the best of our knowledge, never been shown before. On the contrary, other research groups have found decreased NAT activity (N-acetyltransferase, the rate-limiting enzyme step in MT biosynthesis) [36][37][38] when testing the effects of calcium channel blockers in other species. Meyer et al [39] treated baboons with intraperitoneal injections of the calcium antagonists verapamil, nifedipine, nitrendipine and nisoldipine.…”
Section: Discussionmentioning
confidence: 92%
“…However, such stimulatory effect has, to the best of our knowledge, never been shown before. On the contrary, other research groups have found decreased NAT activity (N-acetyltransferase, the rate-limiting enzyme step in MT biosynthesis) [36][37][38] when testing the effects of calcium channel blockers in other species. Meyer et al [39] treated baboons with intraperitoneal injections of the calcium antagonists verapamil, nifedipine, nitrendipine and nisoldipine.…”
Section: Discussionmentioning
confidence: 92%
“…L‐type calcium channel antagonists have been shown to suppress N ‐acetyltransferase activity at night in chicken retina, 10,29 regulating the synthesis of melatonin. The photoreceptors were well labelled with the antibody to α1d subunits, while they did not show immunoreactivity for α1c subunits and α1f subunits were localized to photoreceptor terminals.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, slowly inactivating L‐type calcium currents have been measured in many retinal cells, including photoreceptors, 1 horizontal cells, 2,3 bipolar cells 4–7 and Müller cells 8 . In addition, dihydropyridine antagonists, which block L‐type calcium channel function, block the release of glutamate in Xenopus photoreceptors, 9 and in chickens, the release of melatonin from photoreceptors is also regulated by an L‐type calcium current 10 …”
Section: Introductionmentioning
confidence: 86%
“…Although a role of calcium in the regulation of NAT activity and melatonin production as a result of alterations in intracellular concentrations of cyclic AMP has been suggested [Wilkinson, 1976;Zatz, 1989;Zawilska et al, 1992;Gasser and Gern, 1997], several lines of evidence indicate that calcium may regulate NAT activity and melatonin levels beyond the accumulation of cyclic AMP, i.e., affecting melatonin synthesis by directly regulating the production of NAT [Romero et al, 1975;Zatz and Romero, 1978;Harrison and Zatz, 1989;Zatz and Mullen, 1988;Zhan-Poe and Craft, 1999]. Under ordinary conditions, cyclic AMP mediates the induction of NAT by affecting both mRNA and protein synthesis [Romero et al, 1975;Zatz et al, 1976].…”
Section: Discussionmentioning
confidence: 99%